Utilization of Core Oil Palm Trunk Waste to Methyl Levulinate: Physical and Chemical Characterizations - Abu Jahar N.; Pua F.-L.; Chyi W.J.; Mostapha M.; Zakaria S.; Chia C.H.; Syed Jaafar S.N. (Springer Netherlands, 2023)
Biofuels; Blending; Cellulose; Chlorine compounds; High performance liquid chromatography; Liquid sugar; Nuclear magnetic resonance spectroscopy; Palm oil; Bio-chemicals; Chemical characterization; Extraction method; Free sugar; Lignocellulosic wastes; Methyl levulinate; Oil palm trunk wastes; Oil palm trunks; Extraction